Knowledge and Attitudes of Preschool Teachers about Speech and Language Disorders in Turkey - Uysal, Ayşe Aydin; Güdük, Ayşe Hicret; Tura, Gülşah (Asian Journal of Education and Training, 2019)
The number of people with speech and language disorders is increasing every day (McLeod and McKinnon, 2007). Preschool teachers play a key role in diagnosing and treatment of these disorders since children acquire speech and language abilities rapidly in the preschool period. Speech and language therapy is a new discipline in Turkey. Therefore, the aim of this study is to determine the knowledge levels of preschool teachers in Turkey about children with speech and language disorders. The sample consisted of 153 preschool teachers from Kocaeli, Turkey and a self-administered Teacher Knowledge of Speech/Language Impairment Questionnaire was completed by the participants. Results revealed that knowledge and awareness levels of preschool teachers about children with speech/language impairment are limited. While 46% of the participants report that they have little or no experience with speech/language impaired children and do not feel themselves adequate in teaching children with severe language problems. Workshops designed for preschool teachers about speech and language disorders may offer opportunities to learn about the resources and classroom strategies that are proven successful in teaching students with speech and language disorders in Turkey.